Effects of barfi mRNA knockdown on cell growth and survival in EBV-associated cancer cells / Taznim Begam Binti Mohd Mohidin - Mohd Mohidin, Taznim Begam (2014)

(untitled)
The Epstein-Barr virus (EBV)-encoded BARF1 (BamHI-A rightward frame-1) is expressed in EBV-positive malignancies such as nasopharyngeal carcinoma, EBV-associated gastric carcinoma, B cell lymphoma and nasal NK/T-cell lymphoma, and has been shown to have important role in oncogenesis. However, the mechanism by which BARF1 elicits its biological effects on EBV-positive malignant cells is unclear. In this study, the effects of BARF1 gene silencing on cell proliferation and apoptosis were investigated in EBV-positive malignant cells. We observed that silencing of BARF1 using RNAi significantly inhibits cell proliferation and induces apoptosis-mediated cell death by collapsing the mitochondrial membrane potential in AG876 and Hone-Akata cells. BARF1 knockdown also upregulates the expression of pro-apoptotic proteins and downregulates the expression of anti-apoptotic proteins. In BARF1-downregulated cells, the Bcl-2/BAX ratio is decreased. The caspase inhibitor z-VAD-fmk was found to rescue siBARF1-induced apoptosis in these cells. Immunoblot analysis showed significant increased levels of cleaved caspase 3 and caspase 9. Using western blotting analysis, we also observed a significant increase in cytochrome c level in the cytosolic fractions of BARF1-depleted cells. Immunoprecipitation and further immunoblot analysis revealed that depletion of BARF1 activated formation of apoptosome complex in BARF1-silenced cells. In conclusion, siRNA-mediated BARF1 downregulation induced caspase-dependent apoptosis via the mitochondrial pathway through modulation of Bcl-2/BAX ratio in AG876 and Hone-Akata cells. Targeting BARF1 using siRNA has potential to be developed as a novel therapeutic strategy in treatment of EBV-associated malignancies.